A Single Nucleotide Deletion in an ABC Transporter Gene Leads to a Dwarf Phenotype in Watermelon - Zhu, Huayu; Zhang, Minjuan; Sun, Shouru; Yang, Sen; Li, Jingxue; Li, Hui; Yang, Huihui; Zhang, Kaige; Hu, Jianbin; Liu, Dongming; Yang, Luming (Frontiers in Plant Science, 2019)
The dwarf phenotype is one of the important traits for plant architecture, and it can increase plant density and land utilization especially for protected cultivation. Several dwarf genes have been identified in watermelon, but most of them were not mapped or cloned. In this study, the Cldw1 gene was primary mapped on watermelon chromosome 9 by bulked segregate analysis (BSA-seq) using F2 plants derived from the cross of a normal line WT4 and a dwarf line WM102. The candidate region identified by BSA-seq was subsequently validated and confirmed by linkage analysis using 30 SSR markers in a F2 population with 124 plants. The Cldw1 gene was further fine mapped in a large population with 1053 F2 plants by chromosome walking, and it was delimited into a candidate region of 106 kb. There were six gene predicted in the candidate region and only the gene Cla010337 was identified with two SNPs and a single nucleotide deletion in the coding region in WM102. A dCAPS marker was developed from the single nucleotide deletion which showed co-segregation with dwarf character in the F2 population and 166 natural watermelon germplsms. Cla010337 encoded an ATP-binding cassette transporter (ABC transporter) protein and the expression level of Cla010337 was significantly reduced in all the tested tissues in the dwarf line. The results of this study will be helpful for better understanding the molecular mechanism of dwarf plant regulation in watermelon and marker-assisted selection (MAS) in developing new dwarf cultivars.